Health effects of pesticide among vegetable farmers and the adaptation level of integrated pest management program in Nepal, 2013. (2016)
SUMMARY: Introduction: Exposure to pesticides has been growing as a major public health challenge in developing countries. Overuse and misuse of pesticides have several acute and chronic adverse health consequences. Government of Nepal has implemented Integrated Pest Management (IPM) program to minimize the use of pesticides over the country, however farmers misuse and overuse pesticides in an agriculture sector. Organophosphate insecticide is commonly used pesticide in Nepal which inhibits the neurotransmitter acetyl cholinesterase and affects the central and peripheral nervous system. Organophosphate and organochlorine affect the endocrine system which can lead to diabetes mellitus. Apart from the limited information available on pesticide exposure from small scale studies, there do not exist large scale population level studies. Also, limited information exists on health hazards of pesticides. This study was designed to assess pesticide exposure level and its health effects and further to assess the adaptation process of Integrated Pest Management in Nepal. Materials & methods: A cross-sectional study was conducted during July 2013 to June 2014, with data collection spread from January 2014 to April 2014. Prior to data collection, ethical approval was sought from the independent Ethical Review Board of the Nepal Health Research Council. A sample size of 660 was calculated. Mix method (Qualitative and Quantitative) was used to collect data and two stage cluster sampling was applied using a mix of probability proportionate to size (PPS) and a simple random sampling using the sampling frame from the Annual Progress Report of Potato, Vegetable and Masala Development Program 2011 to select the participants. Primary sampling unit of this study was vegetable program. There were a total of 168 vegetable programs running across 75 districts of Nepal. Out of the total 168 vegetable programs, 15 vegetable programs were selected using PPS sampling method. A vegetable program covers two to ten vegetable pockets. Vegetable pocket was considered as a secondary sampling unit (SSU) in this study. Two vegetable pockets were selected with simple random sampling. Eligible farmers working in selected vegetable pockets listed in alphabetical order and 22 farmers were selected from one vegetable pocket using simple random sampling. Individual face to face interview was conducted using structured questionnaire. Physical and biological measurement was done to assess the health effect of pesticide among vegetable farmers of Nepal. Focus Group Discussion (FGD) was done among IPM trained farmers and structured questionnaires were applied with two key personnel of the District Health Office to assess the adaptation level of IPM based on Diffusion Theory of Innovation. The questionnaires covered information on demographic, pesticide practice, handling procedure and pesticide knowledge of participants. Physical measurements included height and weight, which was measured by validated equipments. Biochemical measurements included blood glucose and AChE levels by dry method and ellmen method respectively. Quantitative data were analysed using the SPSS version 16.0. Qualitative data were analyzed using content analysis. Results:Around two-fifths (38.4%) of participants were engaged in commercial farms for more than ten years. Less than one fourth of participants had not attended IPM training. Fungicide and insecticides were common pesticides used by vegetable farmers in Nepal. Nearly 60% of the participants used fungicides, 42.5% used organophosphate, and 27% used pyrethriod. Potato, tomatoes, cauliflowers, cabbage, beans, tomato, ladyfinger, bitter gourd, pumpkin, cucumber and bottle gourd are the top main cash crops in Nepal. The frequency of applying pesticides in these crops was about five applications per cropping season. Around 97% participants had good knowledge regarding adverse health effects of the pesticides, however 12% did not use any types of Personal Protective Equipments (PPEs), on an average, farmers used two PPEs (non chemical resistant) while spraying the pesticides. Around 53% farmers did not follow the instruction written on the label and sprayed based on their previous experience. Two of the three participants knew about basic principle of IPM however, only one- fourth participants followed its principle and procedure during cultivation of crops. Around 83% participants keep pesticide in the general store where a child can easily reach. Nearly half of the participants throw the pesticide containers anywhere. Around 13% participants used to leak spray during application of pesticides. Half of the participants complained about the acute toxicity syndrome after spraying the pesticides. About 80% of them took rest after appearing such syndromes; very few participants (9%) went to the hospital or health center for treatment. The prevalence of self reported chronic disease was 10% and among them majority reported chronic neuropathic problem. Prevalence of diabetes, including those on medication was 4.5% among vegetable farmers of Nepal. Prevalence of low AChE level was 10.3%. The prevalence of anemia was 53.3% among female participants and 43.9% among male participants. No significant association was found between feeling of illness in the last month and use of PPEs with age category, history of engagement in agriculture, using IPM and sex. However, in multiple linear regression, age and sex was significantly associated with Acetyl cholinesterase. The perception among farmers and official personnel regarding IPM was satisfactory. In the reference of the Theory of Diffusion on Innovation, an adaptation process of IPM was found slow in Nepal. Conclusion :The study demonstrates that the application of pesticide was observed to be widely applied in agricultural sectors of Nepal. Vegetable farmers had considerable knowledge regarding health impacts of pesticide. However, they did not adopt the safety precaution resulting higher risk of exposure with pesticide intoxication. Organophosphate exposures were not sufficiently observed in depressed AChE in Nepal. The prevalence of diabetes was also found high. Large numbers of farmers cultivated crops with traditional technique rather than Integrated Pest Management technique. Perception among farmers and official personnel regarding Integrated Pest Management was moderate. In the reference of the theory of diffusion on innovation, an adaptation process of Integrated Pest Management was found slow in Nepal. There is an urgent need to develop the proper mechanism to monitor the pesticide level in vegetables to reduce the health impact of pesticide among farmers and consumers.